UPAYA LAYANAN PENDIDIKAN PESANTREN SELAMA MASA TRANSISI MENUJU ENDEMI COVID-19 - Hidayat, Rizal; Isnaini, Rohmatun Lukluk (Jurnal Manajemen Pendidikan, 2022)
Over time the handling of covid is getting better, although in its implementation there are still problems from educational institutions that have to re-regulate the order of education. Likewise with the environment of Pesantren, entering the endemic period of the pesantren environment began to make various preparations to be able to return to face-to-face activities, preparations were made as a form of protocol to stay safe and inhibit the spread of existing ones. This preparation is a step towards dealing with the problem of the educational order. This research aims to find out the services provided by islamic boarding schools to their students duringthe face-to-face teaching process that takes place during the transition to endemic. This research is an exploratory qualitative, with a type of field research. Exploratory qualitative research to understand events, actions, and processes in the context of life. peliti carried out data collection with observations, interviews and documentation on several activities and informants at one of the Pesantren huts on madura island which lasted for eight months. The results of the study, namely 1) Theinhibition of activities outside the Islamic boarding school, 2) Theleveling of sick students every week to be treated immediately by the health department, 3) the provision of vitamins or supplements to good students. as well as the pick-up of students outside the island of J awa, especially those who will return to pesantren.